2021
DOI: 10.3390/mi12070808
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Anticancer Drug Monitoring by ds-DNA-Based Electrochemical Biosensor in Clinical Samples

Abstract: In this research, glassy carbon electrode (GCE) amplified with single-wall carbon nanotubes (SWCNTs) and ds-DNA was fabricated and utilized for voltammetric sensing of doxorubicin with a low detection limit. In this technique, the reduction in guanine signal of ds-DNA in the presence of doxorubicin (DOX) was chosen as an analytical factor. The molecular docking study revealed that the doxorubicin drug interacted with DNA through intercalation mode, which was in agreement with obtained experimental results. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 55 publications
1
12
0
1
Order By: Relevance
“…In this sense, Kulikova et al [40] mention that the changes in the current caused by Dox depend on the amount of DNA detected. On the other hand, our results show that the incubation time with Dox is sufficient to indicate the detection process of the double-stranded DNA, as reported by Hassani Moghadam et al [41] where they confirmed that in 20 minutes Dox intercalates the doublestranded DNA. Moreover, Ma et al [42] obtained similar results to ours.…”
Section: Electrochemical Detectionsupporting
confidence: 87%
“…In this sense, Kulikova et al [40] mention that the changes in the current caused by Dox depend on the amount of DNA detected. On the other hand, our results show that the incubation time with Dox is sufficient to indicate the detection process of the double-stranded DNA, as reported by Hassani Moghadam et al [41] where they confirmed that in 20 minutes Dox intercalates the doublestranded DNA. Moreover, Ma et al [42] obtained similar results to ours.…”
Section: Electrochemical Detectionsupporting
confidence: 87%
“…Nevertheless, high sensitivity of the response to doxorubicin can be mentioned. The LOD found was lower than the characteristics of DNA sensors based on redox active polymers of carbonaceous nanomaterials, where the doxorubicin reaction resulted in changes in intrinsic redox activity of the layer (poly(Azure B), 90 pM [39]; poly(neutral red), 100 pM [40]; carbon nanotubes-polylysine, 100 nM [41]; and single-walled carbon nanotubes 60, pM [42]). It should be noted that the reaction with doxorubicin was used in this study to confirm the introduction of DNA in the surface layer and its interaction with the TC molecules.…”
Section: Hydroquinonementioning
confidence: 76%
“…42 Also, DOX is particularly suitable for loading on DNA-based nanocarriers because it intercalates into the minor groove of double-stranded DNA. 43 The low pH in tumor microenvironment (TME) is shared by healthy joints, 44 intracellular milieu, 11 and the stomach. pH-responsive drug release lacks tumor specificity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…DOX is commonly used to as a model drug to test the drug delivery system owing to its excellent antitumor effect and fluorescence property . Also, DOX is particularly suitable for loading on DNA-based nanocarriers because it intercalates into the minor groove of double-stranded DNA . The low pH in tumor microenvironment (TME) is shared by healthy joints, intracellular milieu, and the stomach.…”
Section: Resultsmentioning
confidence: 99%